Design, Synthesis and Anticancer Evaluation of Imidazo Pyridine Fused Thiazole Derivatives - Abdul, Sherin; Vadivel, Velmurugan (Asian Journal of Chemistry, 2026)
Breast cancer remains a major global health burden, driving the need for new therapeutic agents with improved efficacy and safety. In this study, a novel library of imidazopyridine-fused thiazole derivatives (4a-j) was rationally designed, synthesised and tested for anticancer efficacy using the MCF-7 breast cancer cell line. The design combined two well-established pharmacophores imidazopyridine and thiazole to enhance cytotoxic potential through synergistic structural features. The synthesis followed a four-step pathway starting from 2-(6-methyl-2-(p-tolyl)imidazopyridin-3-yl) acetonitrile. Base hydrolysis generated acetic acid (1), which was coupled with ethyl 2-aminothiazole-5-carboxylate using TBTU to form intermediate (2). Subsequent hydrolysis yielded acid (3), which underwent EDAC/HOBt-mediated amide coupling with various benzylamines to afford derivatives 4a-j. All the compounds were characterized by IR, 1H and 13C NMR and mass spectrometry. Molecular docking on human Akt kinase (PDB: 7NH5) showed favourable binding across the series. Compound 4f showed the strongest predicted Akt affinity (-10.024 kcal/mol), followed by 4i, 4g and 4d, though all remained weaker than the reference inhibitor borussertib (-12.63 kcal/mol). In vitro MTT assays revealed significant cytotoxicity for compounds 4i, 4e and 4b, with IC50 values of 35.85, 60.84 and 64.69 µM, respectively. Among them, compound 4i emerged as the most promising lead for further optimisation and mechanistic investigation.